A Kinetic Difference Between 12C‐ and 13C‐Bound Oxygen Exchange Rates Results in Decoupled δ18O and Δ47 Values of Equilibrating DIC Solutions - Philip T. Staudigel; Peter K. Swart (Geochemistry, Geophysics, Geosystems, 2018)
Abstract Accurate determination of paleotemperatures using carbonate δ18O and Δ47 values rely upon the assumption that the minerals in question formed close to expected isotopic equilibrium with their environment. If there is insufficient time for dissolved carbonate to equilibrate with water between the production of DIC and mineralization, the mineral may preserve a disequilibrated isotopic state. The equilibrium composition and rate of DIC equilibration are related to the temperature, pH, and salinity of the solution, and these have been quantified in previous studies which investigated this via the quantitative precipitation all dissolved carbonate species (∑DIC) as barium carbonate (BaCO3). Here we present a study wherein the equilibration over time of clumped isotopes (Δ47) is investigated at 5, 15, and 25 °C. Results show a significant non–first‐order behavior for this process, which can be explained with a kinetic isotope effect wherein oxygen bound to 12C will exchange more rapidly than oxygen bound to 13C. This difference in equilibration rates is minor, less than 2%; however, it results in Δ47 values paradoxically becoming initially less equilibrated during initial equilibration. The magnitude and direction of this effect is expected to vary depending on the direction from which δ18O values equilibrate, even in circumstances where the initial and final Δ47 values are identical. The implication of this finding is that carbonates which form rapidly can have decoupled δ18O and Δ47 values. This study presents a mathematical framework wherein this behavior can be described accurately to provide a predictive model for describing equilibrating aqueous systems.